The influence of concomitant hammertoe correction on postoperative outcomes in patients undergoing hallux valgus correction. Issue 7 (October 2022) - Rajan, Lavan; Kim, Jaeyoung; An, Tonya; Fuller, Robert; Zhu, Jiaqi; Pinney, Stephen J.; Ellis, Scott J.
Abstract: Background: Patients with hallux valgus often develop secondary hammertoe deformities of the lesser toes. Operative management of bunions with hammertoe can be more extensive; however, it is unclear whether this affects patient-reported outcomes. The aim of this study was to compare postoperative patient-reported outcome measures and radiographic outcomes between patients who underwent isolated bunion correction and patients who underwent simultaneous bunion and hammertoe correction. Methods: Preoperative, postoperative, and change in Patient-Reported Outcomes Measurement Information System (PROMIS) scores were compared between patients who underwent isolated hallux valgus correction and those who underwent concomitant hammertoe correction. Radiographic measures including hallux valgus angle (HVA), intermetatarsal angle (IMA), distal metatarsal-articular angle (DMAA), and Meary's angle were also compared. Targeted minimum-loss estimation (TMLE) was used for statistical analysis to control for confounders. Results: A total of 221 feet (134 isolated bunion correction, 87 concomitant hammertoe correction) with a minimum of 12 months follow-up were included in this study. Both cohorts demonstrated significant improvements in the physical function, pain interference, pain intensity, and global physical health PROMIS domains (all p < 0.001). However, patients in the concomitant hammertoe cohort had significantly less improvements in pain interference and pain intensity (p < 0.01, p < 0.05 respectively). The concomitant hammertoe cohort also had significantly higher postoperative pain interference scores than the isolated bunion cohort (p < 0.01). Radiographic outcomes did not differ between the two groups. Conclusion: While both isolated bunion correction and concomitant hammertoe correction yielded clinically significant improvements in patient reported outcomes and normalized radiographic parameters, patients undergoing simultaneous bunion and hammertoe correction experienced substantially less improvement in postoperative pain-related outcomes than those who underwent isolated bunion correction.